AN ANALYSIS ON ENGLISH SYLLABLE STRESS PLACEMENTS OF THE ENGLISH STUDY PROGRAM STUDENTS - Siska Veronica Veronica; Syafrizal Sabaruddin; Indah Damayanti (Universitas Bengkulu, 2018)
This research concerned with the student’s knowledge on the English syllable stress placements of English Education Study Program Students. This research was a descriptive quantitative research. In this research, a test of English syllable placements was used. The words used in the test items were taken from high frequency of word which consist of 10 questions for each English syllable type. The results of this research shows that the knowledge of the English Education Study Program students on English syllable stress placements was low with 39.3 of the total mean score . Futher more, comparison of the test result among three enrollments of samples shows that the different mean score of the second and fourth semester students was not significant (0.6 points); while the different mean scores of the second and fourth semester with sixth semester students was significant (20 points)